Kritik Terhadap Pengajaran Visualiasi Dan Afirmasi Teologi Kemakmuran Berdasarkan Eksposisi Kejadian 15:5-6 - Sitanggang, Murni Hermawaty (Sekolah Tinggi Teologi Anugrah Indonesia, 2024)
What faith is and how to express it are two essential questions that seem easy but are complicated to answer. According to the prosperity gospel adherents, faith must be expressed through imagining (visualization) and saying (affirmation), as written in Genesis 15:5-6. However, for some groups, this teaching deviates from the truth according to the Bible and is more similar to the law of attraction. This article intends to criticize the visualization concept and to explore what is faith according to Genesis 15:5-6 by using the library research method combined with text exposition. The conclusion is that according to Genesis 15:5-6, true faith focuses on God's will entirely without the help of the power of human thoughts and words. Thus, visualization teaching, apart from being unbiblical, is also humanistic and tends to lead to syncretism.